INTEGRASI KEARIFAN BUDAYA SASAK DALAM PEMBELAJARAN GEOMETRI UNTUK MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR - Fitri Indah Rahmawati; Haifaturrahmah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the integration of Sasak cultural wisdom into geometry learning as an effort to improve elementary students’ learning outcomes. The research employs a Systematic Literature Review (SLR) method, with data sources collected from prominent indexing databases such as Scispace, Elicit, Google Scholar, DOAJ, Scopus, Scite.ai, and Publish or Perish, focusing on publications from 2015 to 2025. The findings indicate that incorporating Sasak cultural elements into geometry learning provides students with more contextual, relevant, and meaningful learning experiences. The integration of local cultural aspects—such as crafts, architecture, and traditional Sasak foods—enriches mathematics instruction by connecting it directly to students’ daily lives, thereby enhancing their engagement and understanding of geometric concepts. Nevertheless, successful implementation requires careful planning and appropriate teaching strategies. Supporting factors, including teacher competence and the availability of adequate learning facilities, must be strengthened, while barriers such as the lack of specific instructional guidelines and limited parental involvement need to be addressed to ensure the effectiveness and sustainability of this approach.ua, harus diatasi agar pendekatan ini dapat diterapkan secara efektif dan optimal.